Ecological Components of Corporate Social Responsibility: Theoretical Background and Practical Implementation - GRAZHEVSKA, Nadiya; MOSTEPANIUK, Alla (Journal of Environmental Management and Tourism; Vol 11 No 5 (2020): JEMT Volume XI Issue 5(45) Fall 2020, 2020)
The paper provides the in-deep analysis of the theoretical background of the necessity and efficiency of the ecological component of corporate social responsibility. The distinguish features of four approaches of corporate social responsibility are identified in order to build a comprehensive view of the evolution of the understanding the vital role of the nature in the context of reaching the long-run goals of business and humanity in general. Additionally, sustainability policies of the most ecologically responsible companies were studied to monitor the specifics of their formulation and the ways to prevent the environmental degradation and climate change. Moreover, the implemented eco-oriented activities by companies were analysed to classify the common activities and to evaluate the level of their involvement. The results indicated the gap between the well-developed theoretical background and the poor participation of business in solving and prevention ecological issues.